1998
DOI: 10.1002/(sici)1520-636x(1998)10:7<667::aid-chir12>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Near-UV, circular dichroism, and fluorescence spectra of a rigid rodlike helical polysilane bearing trietheral moiety in ethanol/water

Abstract: An optically active, rigid rodlike helical polysilane with 6,9,12‐trioxatetradecyl and (S)‐2‐methylbutyl substituents (1) was newly obtained as a very high molecular weight polymer of several million. Due to the presence of trietheral substituent, 1 was readily soluble in a polar solvent such as ethanol and a mixture of ethanol and water, but was insoluble in pure water. Polysilane 1 in pure ethanol at room temperature exhibited an intense and narrow ultraviolet (UV) and circular dichroism (CD) absorptions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 23 publications
(63 reference statements)
3
52
1
Order By: Relevance
“…However, it is noted that chiral alkyl termini (a very small portion of the substituents on the main chain) also affect the overall screw-sense of a main chain with achiral side groups, and that the PSS of 15 was opposite to that of 4 bearing the same (S)-2-methylbutyl side groups (Figure 13). [60,62,63,72] …”
Section: "Sergeants and Soldiers" By Attachment Of Enantiopure Chiralmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noted that chiral alkyl termini (a very small portion of the substituents on the main chain) also affect the overall screw-sense of a main chain with achiral side groups, and that the PSS of 15 was opposite to that of 4 bearing the same (S)-2-methylbutyl side groups (Figure 13). [60,62,63,72] …”
Section: "Sergeants and Soldiers" By Attachment Of Enantiopure Chiralmentioning
confidence: 99%
“…For this purpose, an optically active, rigid rod-like helical polysilylene having 6,9,12-trioxatetradecyl and (S)-2-methylbutyl side groups (17) of high molecular weight (M -w = 7.0 6 10 6 and M -n = 2.9 6 10 6 ) was prepared, [72] as shown in Figure 14. Several workers demonstrated that the introduction of oligoetheral side groups to the flexible polysilylene main chain is able to afford greater solubility in alcohol and water as well as hydrophilic properties, [101, 117 -119] whereas the family of 4 bearing alkyl side group is soluble hydrocarbons and tetrahydrofuran only.…”
Section: Temperature Effectsmentioning
confidence: 99%
“…13 The addition of LiTFMS to a PTMS solution in methanol, ethanol, n-butanol, din-butyl ether, or THF did not result in any ionochromic behavior. PTMS also does not show any significant thermochromism, exhibiting only a gradual blue shift as the temperature decreases.…”
mentioning
confidence: 98%
“…1-Chloro-5-(2-ethoxyethoxy)pentane was isolated by distilling the reaction mixture under vacuum. 13 The chloride (50 g) was reacted with magnesium (3 g) at 75°C. The mixture was added slowly to tetrachlorosilane (18 g) in dry diethyl ether at 40°C.…”
mentioning
confidence: 99%
See 1 more Smart Citation